5
$\begingroup$

In this problem we consider a model of stochastic growth. In particular, consider the following system of SDEs:

\begin{align} dX_t &= Y_t dt + \sigma_XdZ_{1t}\\ dY_t &= -\lambda Y_t dt + \sigma_Y \rho dZ_{1t} + \sigma_Y\sqrt{1-\rho^2}dZ_{2t}\\ X_0 &= 0\\ Y_0 &= 0 \end{align}

where $Z_{1t}$ and $Z_{2t}$ are independent Brownian motions. \

Compute $E_t[(X_{t+T}-X_t)]$ and $E_t[(X_{t+T} - X_t)^2]$ as a functions of $T$ and $Y_t$. To illustrate the difference between short-run and long-run risk, compute:
$\lim_{T \to 0}\frac{E_t[(X_{t+T} - X_t)^2]}{T}$
and $\lim_{T \to \infty}\frac{E_t[(X_{t+T} - X_t)^2]}{T}$ \

$\endgroup$
6
$\begingroup$
  1. The sum of two independent brownian motions is also a brownian motion (which is formally proved here)

  2. First of all we solve for $Y_t$. We notice that $d\bigl( Y e^{\lambda t} \bigr) = dY e^{\lambda t} + \lambda Y e^{\lambda t}$.

\begin{align} dY_t &= -\lambda Y_t dt + \sigma_Y \rho dZ_{1t} + \sigma_Y \sqrt{1 - \rho^2} dZ_{2t} \\ &= -\lambda Y_t dt + \sigma_Y dW_t \\ dY_t + \lambda Y dt &= \sigma_Y dW_t \\ d\bigl( Y_t e^{\lambda t} \bigr) &= e^{\lambda t} \sigma_Y dW_t \\ \Bigl[ Y_t e^{\lambda t} \Bigr]^T_0 &= \sigma_Y \int^T_0 e^{\lambda t} dW_t \\ Y_T &= \sigma_Y e^{-\lambda T}\int^T_0 e^{\lambda t} dW_t \\ \end{align}

Where I've defined $W_t = \rho Z_{1t} + \sqrt{1 - \rho^2} Z_{2t}$. This is gaussian distributed with an expectation of 0 and a variance ${\frac {\sigma^2_Y} {2 \lambda}} \bigl( 1 - e^{-2\lambda T} \bigr)$ coming from the Ito isometry

Now plugging this in and solving for $X_t$:

\begin{align} dX_t &= Y_t dt + \sigma_X dZ_{1t} \\ &= \bigl( \sigma_Y e^{-\lambda t}\int^t_0 e^{\lambda s} dW_s \bigr) dt + \sigma_X dZ_{1t} \\ \Bigl[ X_t \Bigr]^T_0 &= \sigma_Y \int^T_0 e^{-\lambda t} \bigl( \int^t_0 e^{\lambda s} dW_s \bigr) dt + \sigma_X Z_{1t} \end{align}

We can solve $\int^T_0 e^{-\lambda t} \bigl( \int^t_0 e^{\lambda s} dW_s \bigr) dt$ using stochastic integration by parts, as done here, using $A = \int^t_0 e^{-\lambda s} ds$ and $B = \int^t_0 e^{\lambda s} dW_s$ gives

\begin{align} \Bigl[ A_t \cdot B_t \Bigr]^T_0 &= \int^T_0 e^{-\lambda t} \bigl( \int^t_0 e^{\lambda s} dW_s \bigr) dt + \int^T_0 \bigr( \int^t_0 e^{-\lambda s} ds \bigr) e^{\lambda t} dW_t \\ \int^T_0 e^{-\lambda t} \bigl( \int^t_0 e^{\lambda s} dW_s \bigr) dt &= -\int^T_0 \bigr( \int^t_0 e^{-\lambda s} ds \bigr) e^{\lambda t} dW_t + \bigl( \int^T_0 e^{-\lambda s} ds \bigr) \cdot \bigl( \int^T_0 e^{\lambda t} dW_t \bigr) \\ &= -{\frac {1} \lambda}\int^T_0 (e^{\lambda t} - 1) dW_t + {\frac {1} \lambda} (1 - e^{-\lambda T}) \int^T_0 e^{\lambda t} dW_t \\ &= -{\frac {1} \lambda}\int^T_0 (e^{\lambda t} - 1) - e^{\lambda t}(1 - e^{-\lambda T}) dW_t\\ &= {\frac {1} \lambda}\int^T_0 \bigl(1 - e^{-\lambda (T-t)} \bigr) dW_t \end{align}

And substituting this in above, we have \begin{align} X_T &= {\frac {\sigma_Y} \lambda}\int^T_0 \bigl(1 - e^{-\lambda (T-t)} \bigr) dW_t + \sigma_X Z_{1T} \end{align}

This is the sum of two (correlated) gaussians, so it is also a gaussian as required

  1. From above, we have

\begin{align} \Bigl[ Y_s e^{\lambda s} \Bigr]^{T+t}_t &= \sigma_Y \int^{T+t}_t e^{\lambda s} dW_s \\ Y_{T+t} &= e^{-\lambda T} Y_t + e^{-\lambda (T+t)} \sigma_Y \int^{T+t}_t e^{\lambda s} dW_s \end{align}

Conditioning on $Y_t$, we can now find $X_{T+t}$ as above

\begin{align} {\mathbb E}\bigl[(X_{T+t} - X_t \bigr)] &= {\mathbb E}\bigl[ \int_t^{T+t} dX_s \bigr] \\ &= {\mathbb E}\bigl[\int^{T+t}_t Y_s ds + \int^{T+t}_t \sigma_X dZ_{1s} \bigr]\\ &= {\mathbb E}\bigl[\int^{T+t}_t Y_s ds\bigr]\\ &= {\mathbb E}\bigl[\int^{T}_0 Y_{u+t} du\bigr] \\ &= {\mathbb E}\bigl[\int^{T}_0 \Bigl( e^{-\lambda u} Y_t + e^{-\lambda (u+t)} \sigma_Y \int^{u+t}_t e^{\lambda s} dW_s \Bigr) du \bigr] \\ &= {\mathbb E}\bigl[\int^{T}_0 e^{-\lambda u} Y_t du \bigr]\\ &= {\frac 1 {\lambda}} Y_t \bigl( 1 - e^{-\lambda T} \bigr) \end{align}

(where I've changed variables from $s$ to $u = s - t$) which makes sense - $Y_t$ is mean-reverting so we expect future values to be closer to zero than current values

\begin{align} {\mathbb E}\bigl[(X_{T+t} - X_t \bigr)^2] &= {\mathbb E}\bigl[ \bigl( \int_t^{T+t} dX_s \bigr)^2 \bigr] \\ &= {\mathbb E}\bigl[\Bigl(\int^{T+t}_t Y_s ds + \int^{T+t}_t \sigma_X dZ_{s1} \Bigr)^2 \bigr]\\ &= {\mathbb E}\bigl[\bigl( \int^{T+t}_t Y_s ds \bigr)^2 + \int^{T+t}_t \sigma_X^2 dt + 2 \int^{T+t}_t Y_s ds \int^{T+t}_t \sigma_X dZ_{1s} \bigr]\\ &= {\frac {Y_t^2} {\lambda^2}} \bigl( 1 - e^{-\lambda T} \bigr)^2 + \sigma_X^2 T + 2 {\mathbb E}\bigl[ \int^{T+t}_t Y_s ds \int^{T+t}_t \sigma_X dZ_{1s} \bigr] \end{align}

For clarity I break out the last term separately: \begin{align} {\mathbb E}\bigl[ \int^{T+t}_t Y_s ds \int^{T+t}_t \sigma_X dZ_{1s} \bigr] &= {\mathbb E}\bigl[ \int^T_0 Y_{u+t} du \int^T_0 \sigma_X dZ_{u1} \bigr] \\ &= {\mathbb E}\bigl[ \int^T_0 \Bigl( e^{-\lambda u} Y_t + e^{-\lambda (u+t)} \sigma_Y \int^{u+t}_t e^{\lambda s} dW_s \Bigr) du \int^T_0 \sigma_X dZ_{1u} \bigr] \\ &= {\mathbb E}\bigl[ \int^T_0 \Bigl( e^{-\lambda (u+t)} \sigma_Y \int^{u+t}_t e^{\lambda s} dW_s \Bigr) du \int^T_0 \sigma_X dZ_{1u} \bigr] \\ &= {\mathbb E}\bigl[ \int^T_0 \Bigl( e^{-\lambda (u+t)} \sigma_Y \int^{u+t}_t e^{\lambda s} \rho dZ_{1u} \Bigr) du \int^T_0 \sigma_X dZ_{1u} \bigr] \\ &= {\frac {\rho \sigma_Y} {\lambda}} {\mathbb E}\bigl[ \int^T_0 \bigl( 1 - e^{-\lambda T} \bigr) dZ_{1u} \int^T_0 \sigma_X dZ_{1u} \bigr] \\ &= {\frac {\rho \sigma_X \sigma_Y} {\lambda}} \int^T_0 \bigl( 1 - e^{-\lambda T} \bigr) du\\ &= {\frac {T \rho \sigma_X \sigma_Y} {\lambda}}\bigl( 1 - e^{-\lambda T} \bigr) \end{align}

and plugging this back in to the block above we have \begin{align} {\mathbb E}\bigl[(X_{T+t} - X_t \bigr)^2] &= {\frac {Y_t^2} {\lambda^2}} \bigl( 1 - e^{-\lambda T} \bigr)^2 + \sigma_X^2 T + 2 {\frac {T \rho \sigma_X \sigma_Y} {\lambda}} \bigl( 1 - e^{-\lambda T} \bigr) \end{align}

Thinking about the behaviour of this process as $T \to \infty$, we see that the $( 1 - e^{-\lambda T})$ terms go to zero and we're left with a variance of $\sigma_X^2 T$, which is just standard geometric brownian motion's variance.

As $T \to 0$, $( 1 - e^{-\lambda T}) \to \lambda T$ which cancel out all of the $\lambda$s so the expression becomes \begin{align} {\frac 1 T} \lim_{T \to 0} {\mathbb E}\bigl[(X_{T+t} - X_t \bigr)^2] &= Y_t^2 T + \sigma_X^2 - 2 \rho \sigma_X \sigma_Y T \end{align}

so as expected, short term variance at $t$ increases with the level of $Y_t$, and decreases if the processes are more positively correlated.

Wow what a question!

$\endgroup$
3
  • 2
    $\begingroup$ Great answer! People like you contribute a lot to make this site better. $\endgroup$ – rvignolo Oct 17 '20 at 3:24
  • 1
    $\begingroup$ Good answer! But a minor typo:$dX_{t} = Y_{t}\, dt + \sigma_{X}\, dZ_{t}^{(1)}$ (not $-\lambda Y_{t}\, dt$). This leads to an answer of $\mathbb{E}_{t}[X_{t+T}-X_{t}] = \frac{1}{\lambda}Y_{t}(1-e^{-\lambda T})$. $\endgroup$ – Christopher K Nov 26 '20 at 17:34
  • $\begingroup$ Thanks, good spot. Let me correct that. $\endgroup$ – StackG Nov 28 '20 at 2:45
2
$\begingroup$

Great problem! First recall that

$$\begin{cases} dY_{t} = -\lambda Y_{t}\, dt + \sigma_{Y} \rho \, dZ_{t}^{(1)} + \sigma_{Y}\sqrt{1-\rho^{2}}\, dZ_{t}^{(2)} \\ Y_{0} = 0. \end{cases}$$ Use It^o calculus to show that $d(e^{\lambda t}Y_{t}) = \sigma_{Y}e^{\lambda t} dW_{t},$ where $W_{t} = \rho \, dZ_{t}^{(1)} + \sqrt{1-\rho^{2}}\, dZ_{t}^{(2)}$ is standard Brownian motion (keep in mind that $d[W_{t},Z_{t}^{(1)}] =\rho\, dt$), and derive $$Y_{t} = \sigma_{Y}e^{-\lambda t} \int_{0}^{t} e^{\lambda s}\, dW_{s}$$ as well as $$X_{t} = \int_{0}^{t} Y_{s}\, ds + \sigma_{X}Z_{t}^{(1)}.$$ We will first compute $\mathbb{E}_{t}[Y_{s}]$ and $\mathbb{E}_{t}[X_{t+T}-X_{t}]$. Since $e^{\lambda t}Y_{t}$ is a martingale, $$\mathbb{E}_{t}[e^{\lambda s}Y_{s}] = e^{\lambda t}Y_{t} \implies \mathbb{E}_{t}[Y_{s}] = Y_{t}e^{\lambda (t-s)},$$ and so \begin{align*} \mathbb{E}_{t}[X_{t+T}-X_{t}] &= \mathbb{E}_{t} \left [\int_{t}^{t+T} Y_{s}\, ds + \sigma_{X}(Z_{t+T}^{(1)}-Z_{t}^{(1)}) \right ] \\ &= \int_{t}^{t+T} \mathbb{E}_{t}[Y_{s}]\, ds \\ &= \int_{t}^{t+T} e^{\lambda(t-s)}Y_{t}\, ds \\ &= \frac{1}{\lambda}Y_{t}(1-e^{-\lambda T}). \end{align*} Now we use It^o isometry to compute $\mathbb{E}_{t}[Y_{s}Y_{r}]$: \begin{align*} \mathbb{E}_{t} \left [e^{\lambda (s+r)}Y_{s}Y_{r} \right ] &= \mathbb{E}_{t} \left [\left (e^{\lambda t}Y_{t} + \sigma_{Y} \int_{t}^{s} e^{\lambda u}\, dW_{u} \right )\cdot \left (e^{\lambda t}Y_{t} + \sigma_{Y} \int_{t}^{r} e^{\lambda v}\, dW_{v} \right ) \right ] \\ &= e^{2\lambda t}Y_{t}^{2} + \sigma_{Y}^{2} \mathbb{E}_{t} \left [\left (\int_{t}^{\min\{s,r\}} e^{\lambda u}\, dW_{u} \right )^{2} \right ] \\ &= e^{2\lambda t}Y_{t}^{2} + \sigma_{Y}^{2} \int_{t}^{\min\{s,r\}} e^{2\lambda u}\, du \\ &= e^{2\lambda t} \left (Y_{t}^{2} + \frac{\sigma_{Y}^{2}}{2\lambda}(e^{2\lambda (\min\{s,r\}-t)}-1) \right ) \end{align*} and so $$\mathbb{E}_{t} [Y_{s}Y_{r}] = e^{-\lambda (s+r-2t)}Y_{t}^{2} + \frac{\sigma_{Y}^{2}}{2\lambda}(e^{-\lambda|s-r|}-e^{-\lambda (s+r-2t)})$$ as well as $$\mathrm{cov}(Y_{s},Y_{r}) = \frac{\sigma_{Y}^{2}}{2\lambda}(e^{-\lambda |s-r|}-e^{-\lambda (s+r-2t)}).$$ Next, calculate for $s \leq r$ \begin{align*} \mathbb{E}_{t} [e^{\lambda s}Y_{s}(Z_{r}^{(1)}-Z_{t}^{(1)})] &= \mathbb{E}_{t} \left [e^{\lambda t}Y_{t}(Z_{r}^{(1)}-Z_{t}^{(1)}) + \sigma_{Y} \int_{t}^{s} e^{\lambda u}\, dW_{u} \cdot \int_{t}^{r} dZ_{v}^{(1)} \right ] \\ &= \sigma_{Y} \rho \int_{t}^{s} e^{\lambda u} \, du \\ &= \frac{\sigma_{Y}\rho}{\lambda}(e^{\lambda s}-e^{\lambda t}) \end{align*} and $$\mathbb{E}_{t} [Y_{s}(Z_{r}^{(1)}-Z_{t}^{(1)})] = \frac{\sigma_{Y}\rho}{\lambda}(1-e^{-\lambda (s-t)}).$$ Finally, \begin{align*} &\mathbb{E}_{t}[(X_{t+T}-X_{t})^{2}] \\ &\quad = \mathbb{E}_{t} \left [\left (\int_{t}^{t+T} Y_{s}\, ds \right )^{2} -2\sigma_{X}(Z_{t+T}^{(1)}-Z_{t}^{(1)})\left (\int_{t}^{t+T} Y_{s}\, ds \right ) + \sigma_{X}^{2}(Z_{t+T}^{(1)}-Z_{t}^{(1)})^{2} \right ] \\ &\quad = \int_{t}^{t+T}\int_{t}^{t+T} \mathbb{E}_{t}[Y_{s}Y_{r}]\, ds\, dr - 2\sigma_{X}\int_{t}^{t+T} \mathbb{E}_{t}[Y_{s}(Z_{t+T}^{(1)}-Z_{t}^{(1)})]\, ds + \sigma_{X}^{2}T \\ &\quad = \int_{t}^{t+T}\int_{t}^{t+T} e^{-\lambda (s+r-2t)}Y_{t}^{2} + \frac{\sigma_{Y}^{2}}{2\lambda}(e^{-\lambda|s-r|}-e^{-\lambda (s+r-2t)})\, ds\, dr \\ &\qquad - \frac{2\sigma_{X}\sigma_{Y}\rho}{\lambda} \int_{t}^{t+T} (1-e^{-\lambda (s-t)})\, ds + \sigma_{X}^{2}T \\ &\quad = \frac{1}{\lambda^{2}}Y_{t}^{2}(1-e^{-\lambda T})^{2} + \frac{\sigma_{Y}^{2}}{2\lambda}\cdot \frac{2(\lambda T + e^{-\lambda T}-1)}{\lambda^{2}} - \frac{\sigma_{Y}^{2}}{2\lambda^{3}}(1-e^{-\lambda T})^{2}\\ &\qquad - \frac{2\sigma_{X}\sigma_{Y}\rho}{\lambda} \left (T - \frac{1}{\lambda}(1-e^{-\lambda T}) \right ) + \sigma_{X}^{2}T. \end{align*} At last, we use asymptotics $\frac{1}{\kappa}(1-e^{-\kappa T}) \sim T - \frac{\kappa}{2}T^{2}$ as $T \rightarrow 0$ to get \begin{align*} & \frac{1}{T} \mathbb{E}_{t}[(X_{t+T}-X_{t})^{2}] \\ &\quad = \frac{1}{T} \left (Y_{t}^{2}T^{2} + \frac{\sigma_{Y}^{2}T^{2}}{2\lambda } - \frac{\sigma_{Y}^{2}T^{2}}{2\lambda } - \frac{2\sigma_{X}\sigma_{Y}\rho}{\lambda} \cdot \frac{\lambda T^{2}}{2} + \sigma_{X}^{2}T \right ) + \mathcal{O}(T^{2}) \\ &\quad = Y_{t}^{2}T + \sigma_{X}^{2} - \sigma_{X}\sigma_{Y}\rho T + \mathcal{O}(T^{2}). \end{align*}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.